Nipah Virus Infection Complicated with Encephalitis and Pneumonia Leading to Fatal Outcome: A Case Report from Bangladesh, January 2024 (Journal of Medicine, 2025)
Nipah virus (NiV) has been a major cause of encephalitis out-breaks with high mortality, primarily in the Indo-Bangladesh regions. Clinical presentations range from asymptomatic infection to acute respiratory infection and fatal encephalitis. Diagnosis can be confirmed by isolation from nucleic acid amplification in the acute phase or antibody detection during the convalescent phase. Treatment is mostly limited to supportive care and syndromic management of acute encephalitis syndrome. Here we discuss a case of middle-aged man from Manikganj district who presented with features of bilateral pneumonia and encephalitis. He progressed to rapid deterioration with development of type 2 respiratory failure of central origin and drop down of GCS to 7/15. Series of investigations revealed encephalitis but causative organism remained undetectable. Clinical suspicion carried out CSF IgM and IgG against NiV.  Positive report and ultimate delayed revealed history of raw palm date sap consumption aided in confirmation of diagnosis. Patient was managed in ICU setting with mechanical ventilation, broad spectrum antibiotics, antiviral and steroid. Unfortunately, patient died on 28 January 2024 at infectious disease hospital.J MEDICINE 2025; 26: 80-84